Influence of the age of Eucalyptus grandis seedlings in the development of Nomophila sp. - Zanuncio, José Cola; Sossai, Marcos Franklin; Zanuncio, Teresinha Vinha; Teixeira, César Augusto Domingues (Pesquisa Agropecuaria Brasileira, 2001)
The influence of the age of Eucalyptus grandis (Myrtaceae) seedlings in the development of Nomophila sp. (Lepidoptera: Pyralidae) was studied. The insect was fed in laboratory at 24±2OC, 80±15% of RH and photophase of 12 hours with 20-30 days or 50-60 days old E. grandis leaves. Observed parameters were: number, duration and characterization of each instar, width of head capsule, length of the body, duration of the larval stage, relationship between number of instars and sex of adults, viability and behavior of Nomophila sp. caterpillars. This insect showed better development with 20-30 days old E. grandis seedlings than those with 50-60 days old E. grandis seedlings, which have harder stems. This reinforces the need to grow Eucalyptus seedlings in good fertility conditions aiming to increase their development which could reduce damage level by Nomophila sp.